Respuesta :

Answer:

Answer=

x=(-2),y=(-4)

and in components form,

(-2,-4)

Step-by-step explanation:

equation1 (-2x+2y=-4)

equation2 (3x+3y=-18)

(times equation 1 by 3 and times equation 2 by 2, to make the y values equal to each other)

E1 (-6x+6y=-12)

E2 (6x+6y=-36)

(subtract both equations from each other)

-6x+6y=-12

-

6x+6y=-36

=(-12x=24)

so, x=24÷-12=-2

(then we sub the value of x into one of the equations- the new one or the old one)

3x+3y=-18

(3×-2)+3y=-18

3y=-18+6=-12

y=-12÷3=-4